PHYSICAL EDUCATION OF CHILDREN OF PRIMARY AND PRESCHOOL AGE (Web of Teachers: Inderscience Research, 2023)
The article describes one of today's most important issues, attention to education and upbringing in preschool educational organizations, state requirements for the development of children of primary and preschool age and coverage of physical education issues in the state program, issues in the field of physical development.